Molecular discrimination of Opisthorchis-like eggs from residents in a rural community of central Thailand. - Saiwasan Buathong; Saovanee Leelayoova; Mathirut Mungthin; Toon Ruang-Areerate; Tawee Naaglor; Picha Suwannahitatorn; Phunlerd Piyaraj; Paanjit Taamasri; Peerapan Tan-Ariya (Public Library of Science (PLoS), 2017)
Opisthorchis viverrini infection is a major public health problem in northern and northeastern Thailand. The chronic infection of O. viverrini is related to cholangiocarcinoma which causes high mortality in endemic areas. Therefore, the diagnosis, treatment, control and prevention of O. viverrini infection are necessary. The morphology of the egg is very similar to that of other species of human liver flukes (Opisthorchis felineus and Clonorchis sinensis) as well as that of small intestinal flukes in the family Heterophyidae. Thus, molecular characterization is crucially required to discriminate species of Opisthorchis-like eggs in fecal examination.We aimed to determine the prevalence of O. viverrini infection among villagers living in Sanamchaikate District, Chachoengsao Province, in central Thailand, where O. viverrini infection has previously been reported. A total of 2,609 fecal samples were examined for Opisthorchis-like eggs using microscopic examination. PCR-RFLP analysis of the ITS2 region was used to discriminate Opisthorchis-like eggs. The genetic structure of O. viverrini infection was demonstrated using nucleotide sequencing of cytochrome c oxidase subunit I (cox1) and NADH dehydrogenase subunit 1 (nad1). Testing of evolutionary neutrality of the cox1 and nad1 sequences of O. viverrini was performed using Tajima's D tests and Fu's Fs tests. Moreover, the haplotype networks and phylogenetic trees were constructed to study the relationships of O. viverrini isolated from different endemic areas. A high prevalence of O. viverrini infection is still observed in a rural community of Chachoengsao Province, central Thailand. The overall prevalence of Opisthorchis-like eggs using microscopic examination was 16.8%. PCR-RFLP profiles showed the predominant infection of O. viverrini (9.6%) including very low infections of other small intestinal flukes, Haplorchis taichui (0.08%) and Euparyphium albuferensis (0.08%). The genetic structure of O. viverrini populations in central Thailand was also described and revealed a non-significant difference in genetic diversity. In addition, the genetic background of the O. viverrini populations was closely related to the isolate from Lao PDR.Our study highlighted the prevalence of O. viverrini infection in central Thailand indicating that control programs and health education regarding opisthorchiasis is still required in this endemic area. Additionally, the study demonstrated the genetic structure of O. viverrini, in central Thailand which could provide information on the molecular epidemiology of this parasite.